Restless Legs Syndrome as the Initial Presentation of Multiple Sclerosis - Ceyla Irkec; Doga Vurallı; Sebnem Karacay Ozkalaycı (Case Reports in Medicine)
The restless legs syndrome (RLS) is a common central nervous system disorder. It is characterized by complaints of unpleasant sensation in the legs occurring during periods of leg inactivity which worsen or only occur in the evening or at night and relieved partially or totally by movement. The RLS may be idiopathic or due to secondary causes. It is associated with several pathological or physiological conditions. Iron metabolism and dysfunctions of the dopaminergic system are the most important factors in the pathophysiology. There are several studies suggesting multiple sclerosis as one of the causes of symptomatic RLS. Here, we report a case of RLS as the initial presentation of MS. The sudden onset of RLS symptoms in our patient suggested the possibility of an underlying cause. His diagnostic evaluation excluded other causes of RLS and his clinical course suggested that RLS was due to MS. MS with the spinal cord involvement is mostly associated with RLS, but any lesion in the hypothalamic-spinal connection may cause disinhibition of lower spinal levels, resulting in RLS. RLS as the initial presentation of MS reflects that the pathophysiology of RLS in MS is related to inflammatory demyelination rather than axonal degeneration.